Statistical modelling of social risk factors for sexually transmitted diseases among female youths in Nigeria - Adebowale, Ayo Stephen; Titiloye, Musibau; Fagbamigbe, Adeniyi Francis; Akinyemi, Odunayo Joshua (The Journal of Infection in Developing Countries, 2013)
Introduction: Sexually Transmitted Diseases (STDs) are avertable, but the social risks factors connected to these infections are often unnoticed by many, particularly female youths. Previous studies on STDs among youths in Nigeria only focused on its risk factors but failed to model these risk factors as evidenced in this study. Methodology: The study is retrospective cross-sectional in design which utilized Nigeria Demographic and Health Survey, 2008. It focused on female youths aged 15-24 (n=8093) who ever had sexual intercourse (vaginal, oral and anal). Data analysis was done using Chi-square and logistic regression models. The logistic regression on the data was performed at two stages. These stages generated three and eight different models respectively. Results: Data analyses revealed that the mean age of the respondents was 20.2±2.5. Female youths who were aged between 20-24 years contacted STDs in the last 12 months (2.5%) than those between the ages of 15-19 months (1.4%). A year prevalence of STDs among female youths in Nigeria was 2.1%. Socio-demographic factors such as age, educational status, wealth index, marital status, toilet shared, place of residence, contraceptive use and total life-time number of sexual partners were found to be associated significant risk factors for contacting STDs (P<0.05). Conclusions: The data confirmed the considerable impact of wealth index and contraceptive use as important predictors of STDs acquisition. Constant use of condoms, abstinence and having one uninfected sexual partner can help reduce the risk of STDs transmission.